2022
DOI: 10.3892/ol.2022.13200
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting therapeutic strategies for ovarian cancer by focusing on redox homeostasis (Review)

Abstract: Recent advances in molecular genetics have expanded our understanding of ovarian cancer. High levels of reactive oxygen species (ROS) and upregulation of antioxidant genes are common characteristic features of human cancers. This review reconsiders novel therapeutic strategies for ovarian cancer by focusing on redox homeostasis. A literature search was performed for preclinical and clinical studies published between January 1998 and October 2021 in the PubMed database using a combination of specific terms. ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 114 publications
(227 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, they also showed that H 2 O 2 treatment induces the degradation of nanoparticles and the drug release rate was significantly increased. The fact that the ROS level is normally elevated in tumor tissue can be used as a targeting issue, and this status induces the tumor-specific degradation of nanoparticles to liberate anticancer agents [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they also showed that H 2 O 2 treatment induces the degradation of nanoparticles and the drug release rate was significantly increased. The fact that the ROS level is normally elevated in tumor tissue can be used as a targeting issue, and this status induces the tumor-specific degradation of nanoparticles to liberate anticancer agents [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, antioxidants protect cells from DNA damage by neutralizing excess ROS (29). A sublethal dose of iron overload participates in mutagenesis and aberrant pro-tumorigenic signaling to activate cell survival and promote carcinogenesis (29,30). Thus, low to moderate oxidative stress may contribute to the development of EAOC (26,27,(29)(30)(31).…”
Section: Current Understanding Of Malignant Transformation Of Endomet...mentioning
confidence: 99%
“…A sublethal dose of iron overload participates in mutagenesis and aberrant pro-tumorigenic signaling to activate cell survival and promote carcinogenesis (29,30). Thus, low to moderate oxidative stress may contribute to the development of EAOC (26,27,(29)(30)(31). This suggests that not only endometriosis but also conditions of iron overload, such as hemochromatosis, viral hepatitis B and C, and asbestos exposure, are risk factors for cancer development (32).…”
Section: Current Understanding Of Malignant Transformation Of Endomet...mentioning
confidence: 99%
See 2 more Smart Citations